Development of Augmented Reality (AR)-Based Educational Media to Improve High School Understanding of Viral Concepts - Amilil `Ulya; Eva Nurul Malahayati; Dhamas Mega Amarlita (Universitas Tidar, 2026)
This study aims to develop and determine the feasibility and effectiveness of Augmented Reality (AR)-based learning media on virus material for 10th- grade high school students. The background of this study is students’ difficulty in understanding the abstract concept of viruses and the limited learning media used by teachers. The method used was Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate), which was implemented on a limited basis at SMAN 1 Kademangan. Data collection was conducted through expert validation, a practicality questionnaire, and response questionnaires for teachers and students. The validation results showed that the developed media was highly feasible, with an average feasibility score of 96%. Practicality tests by students and teachers yielded scores of 93% and 85%, respectively (classified as “very practical”), while effectiveness tests received an 82% response (very positive) from teachers and a 79% response (positive) from students. In conclusion, this AR-based learning medium has proven to be suitable and effective for teaching material on viruses, and can increase student engagement in the learning process through visual and interactive means in line with the demands of 21st- century learning.